Specificity of economical efficiency estimation of the management and marketing tricks - Yu.A. Daynovskyy (Marketing i Menedžment Innovacij, 2012)
Forms of economical efficiency tricks manifestation applied in spheres of management and marketing are studied. New tricks classification by the specificity of an effect obtained and demonstrated is proposed. The necessity of different approaches to the economical efficiency estimation for some groups of tricks is reasoned. Examples of the tricks with different economical efficiency manifestation are made.